Dietary Pyridoxine Requirements of Coho Salmon (Oncorhynchus kisutch) Post-Smolts - Hairui Yu; Xinyue Zhang; Ziyi Yuan; Leyong Yu; Youzhi Zhao; Lingyao Li (Aquaculture Nutrition)
A 10-week feeding trial was conducted to investigate the dietary pyridoxine requirements of coho salmon (Oncorhynchus kisutch) post-smolts with an initial mean body weight of 180.22 ± 0.41 g. Seven diets were prepared with gradient pyridoxine levels of 0.32, 1.25, 2.56, 4.08, 8.24, 16.02, and 32.32 mg/kg, respectively, and each diet was assigned to three replication groups of 10 fish. The results revealed that coho salmon fed the diet with pyridoxine supplementation gained more final body weight (FBW), specific growth rate (SGR), and better feed conversion ratio (FCR). FBW and SGR of the fish fed the diet with 8.24 mg/kg pyridoxine were significantly higher than those of the other groups (P<0.05). An inverse trend was observed for FCR, which was the lowest in fish fed the diet with 8.24 mg/kg pyridoxine. The gradient pyridoxine levels did not yield any statistically (P>0.05) significant impact on the whole-body composition including moisture, ash, crude lipid, and crude protein. The hepatic pyridoxine concentration, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) activities increased significantly with dietary pyridoxine levels increasing from 0.32 to 4.08 mg/kg (P<0.05) and plateaued after that (P>0.05). The coho salmon fed the diet with 8.24 mg/kg pyridoxine achieved the maximum superoxide dismutase and catalase, as well as the minimum total cholesterol, triglyceride, and malondialdehyde. Broken line analysis of SGR, FCR, AST, and ALT activities reflected the optimal dietary pyridoxine requirements for coho salmon post-smolts from 3.92 to 7.08 mg/kg diet.